Molecular identification of microorganisms in agricultural, ornamental and forest crops in Costa Rica, 2009-2018. Part 1 - Blanco-Meneses, Mónica (2022)
Introduction. The Laboratory of Molecular Techniques applied to Phytoprotection (LTM), Crop Protection Research Center, Universidad de Costa Rica; receives agricultural, ornamental, and forest crops for the identification of microorganisms using molecular techniques. Objective. To identify pathogenic and non-pathogenic fungi, oomycetes, and protozoa in agricultural, ornamental, and forest crops in Costa Rica by molecular methods. Materials and methods. Between 2009 and 2018, plant parts (root, stem, leaves, fruits) and other materials such as water, substrate, and soil were received. A total of 805 isolates were obtained for identification of microorganisms by DNA extraction techniques, end-time and real-time PCR and sequencing using molecular markers. Results. The sequencing allowed the identification of a total of 154 species of fungi, 6 oomycetes, and 1 protozoa. Among the fungi identified, genera such as Fusarium predominated with fourteen different species, followed by Colletotrichum and Aspergillus with eleven species identified for each one. In the oomycetes, species of the genus Phytophthora prevailed, and within the protozoa the genus Plasmodiophora. In addition, the scientific references supporting the presence of the microorganisms identified in each particular crop have been included in the information. Conclusion. It was possible to identify by molecular techniques pathogenic and non-pathogenic fungi, oomycetes and protozoa species isolated from different agricultural, ornamental and forest crops in Costa Rica.